Foot ailments during Hajj: A short report - Shruti Sridhar; Samir Benkouiten; Khadidja Belhouchat; Tassadit Drali; Ziad A. Memish; Philippe Parola; Philippe Brouqui; Philippe Gautret (Journal of Epidemiology and Global Health, 2019)
A study of ailments of the feet in pilgrims of Hajj revealed that 31% of them suffered from blisters, and the prevalence was five times higher in females. The presence of comorbidity (diabetes, obesity and advanced age) warrants immediate attention to them to avoid serious complications.